Non-human primate: the new frontier model of female reproductive engineering - Yoon Young Kim; Yoon Young Kim; Jina Kwak; Byeong-Cheol Kang; Byeong-Cheol Kang; Seung-Yup Ku; Seung-Yup Ku; Seung-Yup Ku (Frontiers in Bioengineering and Biotechnology)
Reproductive engineering encompasses a range of advanced tissue engineering techniques aimed at addressing infertility that is non-curable with current assisted reproductive technology (ART). The use of animal models has been crucial for these advancements, with a notable preference for non-human primates (NHPs) given their genetic, anatomical, and physiological similarities to humans. Therefore, NHPs are invaluable for studying reproductive engineering. Thus, in reproductive studies, NHPs bridge the anatomical and physiological gaps between rodent models and humans. Their shared features with humans, such as menstrual cycles, placentation, and hormonal regulation, allow for more accurate modeling of reproductive physiology and pathology. These traits make NHPs indispensable in the exploration of reproductive engineering, including infertility treatments, genetic engineering, and uterine transplantation. Reproductive engineering is a transformative field that addresses infertility and enhances reproductive health. By leveraging the unique traits of NHPs, researchers can deepen their understanding of reproductive processes and refine ART techniques for human use. Advances in genetic engineering have enabled the creation of transgenic NHP models, which have been used to modify genes to investigate roles for various purposes, and the process, as mentioned earlier, is closely related to the ART technique, including fertility, embryogenesis, and pregnancy. Therefore, the relation to reproductive studies and the necessity of the NHP model are prerequisites for reproductive engineering. The engineering of NHPs is critically related to integrating ethical practices and exploring complementary methodologies. This review overviews the types of NHP frequently used and studies using NHP for reproductive engineering. These studies may suggest a broader way to use NHP for reproductive engineering.